2018
DOI: 10.1111/jcmm.14087
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The long non‐coding RNA‐ROR promotes osteosarcoma progression by targeting miR‐206

Abstract: The long intergenic non‐protein coding RNA regulator of reprogramming (lncRNA‐ROR) has been reported to play crucial regulatory roles in the pathogenesis and progression of multiple cancers. However, whether ROR is associated with the initiation and development of osteosarcoma (OS) remains unclear. Here, we found that ROR expression level was significantly up‐regulated in OS tissue samples compared to adjacent normal tissues, and the elevated ROR was closely correlated with advanced tumour‐node‐metastasis (TNM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Consistent with the finding of the present study, previous studies reported impaired levels of miRNAs in various cancer types, including RCC (3234). Furthermore, it was reported that ROR was able to induce the development of osteosarcoma by regulating miR-206 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the finding of the present study, previous studies reported impaired levels of miRNAs in various cancer types, including RCC (3234). Furthermore, it was reported that ROR was able to induce the development of osteosarcoma by regulating miR-206 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNAs have been reported to be involved in the regulation of OS. For example, Fei et al (16) discovered that expression of the lncRNA regulator of reprogramming (ROR) is significantly increased in OS tissues and in OS cell lines, and that upregulation of ROR appears strongly related to tumour stage. Yang et al (23) found that the expression of lncRNA XIST is dramatically elevated in OS tissues and also strongly associated with tumour stage.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a kind of small endogenous RNA that can influence the post-transcriptional regulation of specific genes (15). Increasing attention has been paid to the anti-tumoral roles of miRNAs in OS, such as miRNA (miR)-206 (16), miR-137 (9), and miR-193-3p (10). miR-424-5p is widely considered to be a suppressor in several types of human cancers, such as glioma (17), cholangiocarcinoma (18) and ovarian cancer (19).…”
Section: Introductionmentioning
confidence: 99%
“…Retinoblastoma is a highly malignant tumour that appears in retinal development and is the most common primary intraocular tumour in childhood and infancy 53 . Recent studies have shown that lncRNA‐ROR may contribute to the tumorigenesis and metastasis 54–56 . LncRNA‐ROR is significantly upregulated in retinoblastoma tissues, and its overexpression is significantly correlated with optic nerve invasion, nodal or distant metastasis, and recurrence.…”
Section: Mir‐32 In Cancersmentioning
confidence: 99%
“… 53 Recent studies have shown that lncRNA‐ROR may contribute to the tumorigenesis and metastasis. 54 , 55 , 56 LncRNA‐ROR is significantly upregulated in retinoblastoma tissues, and its overexpression is significantly correlated with optic nerve invasion, nodal or distant metastasis, and recurrence. LncRNA‐ROR modulates the EMT programme by competitively binding to endogenous miR‐32‐5p and regulating Notch signalling pathway activity in retinoblastoma cells; these behaviours may provide new insights into novel molecular therapeutic targets for retinoblastoma.…”
Section: Mir‐32 In Cancersmentioning
confidence: 99%